The Libyan War 1911-1912. - Ungari, Andrea (Cambridge Scholars Publishing, 2013)
The war between Italy and the Ottoman Empire for possession of Cyrenaica and Tripolitania was a crucial event both for Italian domestic and foreign policy and for the contemporary European balance of power. For Italian society the Libyan conflict was in many ways a dress rehearsal for the First World War. The propaganda campaign for the occupation of Libya, orchestrated around the myth of the ""Grande Italia"" and the ""Grande proletaria"" had an important impact on the Italian political system ...